Country‐specific HPV‐related genital disease among men residing in Brazil, Mexico and The United States: The HIM study. Issue 2 (20th October 2016) - Sudenga, Staci L.; Torres, B. Nelson; Fulp, William J.; Silva, Roberto; Villa, Luisa L.; Lazcano‐Ponce, Eduardo; Ingles, Donna J.; Stoler, Mark; Messina, Jane L.; Abrahamsen, Martha; Baggio, Maria Luiza; Salmeron, Jorge; et al.
Abstract : The purpose of this study was to assess whether the incidence of histopathologically confirmed condyloma and penile intraepithelial neoplasia (PeIN) and rates of genital HPV infection progression to these lesions differs by country (Brazil, Mexico and the U.S.). At each visit, lesions were biopsied and were categorized by pathologic diagnoses. The Linear Array genotyping method was used to identify HPV genotypes from genital swabs, while the INNO‐LiPA HPV Genotyping Extra method was used for tissue specimens. Age‐specific analyses were conducted for lesion incidence by country, with Kaplan–Meier estimation of cumulative incidence. The proportion of HPV infections that progressed to condyloma and PeIN, the median time to lesion development and the incidence rates were estimated by country. When comparing demographic and sexual characteristics across the three countries, sexual orientation ( p = 0.008) and lifetime number of female sexual partners ( p < 0.0001) were differentially associated with lesion incidence in the three countries. Condyloma incidence in Brazil and the U.S. decreased with age, while incidence remained constant across the lifespan in Mexico. There were no differences by country and age for PeIN incidence. HPV types 6 and 11 were the most common types to progress to condyloma and HPV types 16, 6 and 11 were the most common types to progress to PeIN in all three countries. The continuous risk of condyloma and PeIN across all age groups and countries in this study emphasizes the need to ensure that strong HPV immunity, such as that obtained through vaccination, is maintained across the lifespan of men. Abstract : What's new? To best set policy for protecting men against HPV, it is valuable to understand patterns of HPV‐related disease. These authors tabulated incidence data from Brazil, Mexico and the United States to find out how often men develop external genital lesions, such as genital warts and penile intraepithelial neoplasia (PeIN). In all three countries, men continued to develop HPV‐related lesions at older ages, 45–70, suggesting that it might be wise to keep up immunizations throughout adulthood. HPV types 16, 6 and 11 were the most likely to progress to lesions.